The Effect of Organizational Commitment, Job Training and Career Development on Employee Performance with Work Competency as a Moderation Variable at PT Pelindo Multi Terminal Branch Dumai - Leo Diffu Wijaya Lumban Gaol; Desi Astuti; M. Chaerul Rizky (Equivalent : Journal of Economic, Accounting and Management, 2026)
This study aims to analyze the influence of organizational commitment, job training, and career development on the performance of employees with work competence as a moderation variable at PT Pelindo Multi Terminal Branch Dumai. This study uses a quantitative approach with a survey method. The research population is all employees of PT Pelindo Multi Terminal Branch Dumai which is 44 people, and the sampling technique uses saturated sampling (census) so that the entire population is used as a research sample. Data were collected through a questionnaire with a Likert scale and analyzed using Partial Least Square - Structural Equation Modeling (PLS-SEM) with the help of SmartPLS software to test the direct relationship and moderation effect between variables. The results of the study show that: (1) Organizational commitment does not have a significant effect on employee performance; (2) Job training does not have a significant effect on employee performance; (3) Career development does not have a significant effect on employee performance; (4) Organizational commitment has a positive and significant effect on work competence; (5) Job training has a positive and significant effect on work competence; (6) Career development has a positive and significant effect on work competence as the most dominant factor with a path coefficient of 0.446; (7) Work competence has a very strong and significant effect on employee performance with a path coefficient of 0.743 (t-statistics = 6.774, p-values = 0.000), making it a key factor in determining performance; (8) Work competencies are not able to moderate the relationship between organizational commitment and employee performance; (9) Job competencies are not able to moderate the relationship between job training and employee performance; (10) Work competencies are not able to moderate the relationship between career development and employee performance.